Literasi Digital Saat Pandemi - Andarini, Firda Aulia; Salim, Herli (Universitas Pendidikan Indonesia Kampus Serang, 2021)
Entering the pandemic era where learning is carried out online, in tracking every learning process, high digital literacy skills can make it easier for students because digital literacy is predicted to be the main and important foundation in the education sector in the future. The research method used in this study is a descriptive research method which aims to describe and explain how to implement digital literacy in online learning during the current Covid-19 pandemic. Researchers conducted research at the SD Pilot Laboratory UPI Serang, the school was chosen because it had met the researchers' criteria to conduct research, namely fully online learning, being active in online learning, and having ICT (Information and Communication Technology) learning. From the interview data that has been carried out by the researcher, information was obtained that digital literacy at the UPI Serang Pilot Laboratory Elementary School has unknowingly been going well, as evidenced by students who have studied ICT lessons and have carried out online learning quite smoothly. In general, the students of SD Laboratoriaum Pilot UPI Serang have implemented digital literacy well with the fulfillment of four aspects, namely basic literacy skills (reading and writing), background knowledge of information (intellectual level), ICT skills, and attitudes and information (perspectives). Based on the results and discussions that have been presented by the researchers, it can be concluded that digital literacy activities during the Covid-19 pandemic at the UPI Serang Pilot Laboratory Elementary School went quite well and smoothly despite experiencing some difficulties.